Cryptosporidiosis in buffalo calves - Bharti, Archana; Swamy, Madhu; Dubey, Amita (Buffalo Bulletin, 2020)
Study was conducted to determine the prevalence of naturally occurring Cryptosporidium spp. parasite in buffalo calves of Jabalpur region and the pathological effects produced by them contributing to calf mortality. 34.21% (13/38) Cryptosporidium oocyst prevalence were found in buffalo calves with Ziehl-Neelsen stain. Maximum 75% (03/04) positive cases were of diarrhoeic calves. More than 05 Cryptosporidium oocyst/ smear (22 mm x 40 mm) were found in 5 faecal samples including 04 diarrhoeic/enteric and 01 non diarrhoeic animals. Maximum 58.33% (07/12) male and 23.07% (06/26) female were revealed the presence of Cryptosporidium spp. The maximum positive cases (06/13) were diagnosed in hot and humid weather. Carcass of buffalo calves found positive for Cryptosporidium spp. were dehydrated with soiled perianal region and anal dilatation. Small intestine appeared congested whereas ballooning was observed in the large intestine and mesenteric lymph nodes were uniformly enlarged.